Ankle anticipatory postural adjustments during gait initiation in healthy and post-stroke subjects. Issue 9 (November 2015) - Sousa, Andreia S.P.; Silva, Augusta; Santos, Rubim
Abstract Background Anticipatory postural adjustments during gait initiation have an important role in postural stability but also in gait performance. However, these first phase mechanisms of gait initiation have received little attention, particularly in subcortical post-stroke subjects, where bilateral postural control pathways can be impaired. This study aims to evaluate ankle anticipatory postural adjustments during gait initiation in chronic post-stroke subjects with lesion in the territory of middle cerebral artery. Methods Eleven subjects with post-stroke hemiparesis with the ability to walk independently and twelve healthy controls participated in this study. Bilateral electromyographic activity of tibialis anterior, soleus and medial gastrocnemius was collected during gait initiation to assess the muscle onset timing, period of activation/deactivation and magnitude of muscle activity during postural phase of gait initiation. This phase was identified through centre of pressure signal. Findings Post-stroke group presented only half of the tibialis anterior relative magnitude observed in healthy subjects in contralesional limb (t = 2.38, P = 0.027) and decreased soleus deactivation period (contralesional limb, t = 2.25, P = 0.04; ipsilesional limb, t = 3.67, P = 0.003) as well its onset timing (contralesional limb, t = 3.2. P = 0.005; ipsilesional limb, t = 2.88, P = 0.033) in both limbs. A decreased centre of pressure displacement backward (t = 3.45, P = 0.002) and toward the first swing limb (t = 3.29, P = 0.004) was observed in post-stroke subjects. Interpretation These findings indicate that chronic post-stroke subjects with lesion at middle cerebral artery territory present dysfunction in ankle anticipatory postural adjustments in both limbs during gait initiation.